Reciprocity and Resilience: Teaching and Learning Sustainable Social Enterprise through Gaming. (April 2015) - Dobson, Stephen; Sukumar, Arun; Ridley-Duff, Rory; Roast, Chris; Abell, Benjamin
Abstract : Against a backdrop of increased global environmental and economic uncertainty, the resilience and sustainability of urban communities is a paramount concern for decision makers. The work presented here aims to explore how teaching and learning around transition initiatives, based upon social enterprise and reciprocity, might be supported by game theory and strategy simulation environments. Key elements for this are the co-evolutionary nature of internal and external organisational contexts. The gaming prototype developed here (Exploring Community Resilience, ExCoRe) is based upon an extension of the Prisoner's Dilemma as a medium for active learning, but is enacted through a multi-player and dynamic environment. The key learning objectives for the game are to introduce a broad concept of reciprocity and collaboration on a systems level, and the importance of an emergent and responsive 'learning strategy' for new start-ups and enterprises. The static nature of the traditional strengths, weaknesses, opportunities, and threats (SWOT) approach is challenged and students are encouraged to appreciate, through establishing game strategy, a much more fluid and dynamic relationship between internal and external environments.